Selection criteria in international subcontracting : An example from the Finnish wood construction industry - Rissanen, Tuukka (fi=Turun yliopisto|en=University of Turku|, 2018)
The construction industry in Finland is booming and it is not unusual to have multiple different subcontractors and nationalities operating in construction sites. In addition, the construction projects are increasingly challenging and new construction methods are introduced, one of which is wood construction which is discussed in this study. Furthermore, the increased complexity of the projects has created unprecedentedly demanding construction sites in terms of management. One important aspect of successful construction project management is the proper selection of a subcontractor that can fulfill the requirements of a project. The purpose of this study is to analyse, based on a theoretical framework and empirical research, what criteria were used in the selection process of an international subcontractor. The example in this study is a Finnish wood construction site where a Norwegian construction firm works as a subcontractor for a Finnish company. The empirical research is based on an interview where the person responsible for the subcontractor selection was interviewed. The objective was to analyse what criteria were used in the selection process and how those criteria were evaluated. In addition, one objective was to find out if there are any notable aspects that were not addressed in the earlier empirical studies on the theme. Findings from the study indicate that earlier empirical research and the chosen theoretical framework are coherent with the results from the interview. When it comes to the selection criteria, the most important criteria were past performance, experience and quality and safety. In addition, the study supports existing research which has suggested that the criteria should always be emphasised and evaluated based on the project specific requirements. The most significant finding was the observed effect of earlier business relation to the selection process. In a situation where the contractor and a subcontractor have a successful cooperative background, the earlier business relation can be used as a reference to evaluate the selection criteria. In other words, the earlier business relation facilitates the selection of an international subcontractor and reduces the extensive evaluation of the selection criteria. The effect of earlier business relation to the use of selection criteria was the most crucial finding that was not addressed in the earlier empirical research on the topic and it should be taken into account in the international subcontracting.